Study on the growth factors and hepatoprotective effect of Beta vulgaris L. in male Wistar rats - Al Nouri, Doha Mustafa; Althalmawi, Hallah Oqalaa; Al Faifi, Latifa Yahiya; Owayedh, Hussah Mohammed Al; Arzoo, Shaista (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The purpose of this study was to investigate the effect of Beta vulgaris L. juice on growth andliver enzymes in male Wistar rats. The experiment was conducted on 15 Wistar albino rats,divided into 3 groups. Group 1 was fed with a standard diet (control group), group 2 was fedwith a standard diet and 1 ml Beta vulgaris L. juice and group 3 was fed with a standard diet and2 ml Beta vulgaris L. juice. Statistically insignificant difference was observed between controland experimental groups for total food consumption. Similarly difference was insignificant forfinal weight but it has been found that change in weight was slightly more in control group whencompared to experimental group fed with 2 ml juice although the change in weight wasinsignificant between control and experimental groups. It has been found that administration ofBeta vulgaris L. decreased the AST and ALT activities in serum so it can be concluded fromthis study that beetroot feeding may protect against liver damage.